Avaliação do responder por exclusão por bebês de até 36 meses - Souza, Leylanne Martins Ribeiro de (Universidade Federal de São Carlos, 2014)
Exclusion responding is the immediate selection of a comparison indefinite stimulus before a stimulus model also undefined, without a prior history teaching model. The acquisition of vocabulary due to exclusion responding can provide the expansion of verbal repertoire without prior training and accelerating the emergence of new relationships between words and referents. This study aimed to verify if the procedures of teaching conditional discriminations for babies favor the occurrence of exclusion responding and of learning of the relation new name new object, and to check how many trials were needed to check the occurrence of learning the new relation. In all two studies (S1 and S2), the procedure consisted of the establishment of auditory-visual conditional discrimination by matching-to-sample (MTS) with familiar stimuli (baseline), exclusion probes, learning probes and control probes. The difference between the procedures was the use of a cardboard box with masking function (comparison-empty) in S1 and sheets of vellum, with mask function, inserted in a notebook of education in S2. Eight 27-36 month-old babies participated in the first study and the aim was to investigate the emergence of exclusion responding and learning relationships that emerged in a play setting. Blocks of ten trials were performed, with the presentation of four comparison stimuli, one of them inside the box / mask. Four participants learned to baseline after retraining. All participants responded by exclusion and four had learning relations that emerged after retraining LB and the probes. It took six to 11 trials to exclude the occurrence of learning new relationships. A five 15-24 month-old babies participated in the second study. Blocks of six trials were performed, with the presentation of two and three comparison stimuli; consequence turned from the continuous reinforcement (CRF) to variable-ratio 2 (VR2) in baseline trials, and the probes were performed in extinction. The mask (comparison-empty) was inserted through fading in terms of education. All infants learned the conditional discrimination and exclusion responding (in the first or second attempt of each probe); however, none of them responded consistently with the criteria of learning relations new name new object. The need to devise new procedures to foster the learning of relationships that emerged in exclusion responding has been discussed.
Assessment of exclusion responding for infants up to 36 months
Keywords: Psicologia; Discriminação condicional; Responder por exclusão; Bebês; Conditional discrimination; Exclusion responding; Babies; CIENCIAS HUMANAS::PSICOLOGIA